PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN RISET DI BUSINESS CENTER PURBALINGGA 3 - Sandi, Kurnia; Hasibuan, Reza Rahmadi; Ulya, Widadatul (Awatara Publisher, 2023)
PT. Herba Penawar Alwahida Indonesia (HPAI) – Halal Network International (HNI) which is one of the Halal Network companies in Indonesia that focuses on herbal products. HNI-HPAI already has 95 types of products, such as herbal medicines, products for daily home use, beauty products, and others. Building customer loyalty is easier and costs less than finding new customers who require more funds. Thus the company must have the right strategy to build the level of customer loyalty. Basically consumers want the quality of the products they buy in accordance with their requests, so companies to build a level of customer loyalty must be product quality oriented. This study aims to examine the effect of product quality and price on loyalty at Business Center 3 Purbalingga. The type of research method used is quantitative method, questionnaire data as many as 60 respondents from consumers of Business Center 3 Purbalingga. The sampling technique used stratified random sampling. Data was taken using a questionnaire which was measured using a Likert scale. This study uses multiple linear analysis with the help of SPSS version 26. The results of this study indicate that each product quality and price variable has a significant effect on customer loyalty.